Swiss DRGs: Patient Heterogeneity and Hospital Payments - Michel Mougeot; Florence Naegelen (Swiss Journal of Economics and Statistics, 2008)
In this paper, we analyze the prospective method of paying hospitals when the within-DRG variance is high. To avoid patients dumping, an outlier payment system is implemented. In the APDRG Swiss System, it consists in a mixture of fully prospective payments for low costs patients and partially cost-based system for high cost patients. We show how the optimal policy depends on the degree to which hospitals take patients' interest into account. A fixed-price policy is optimal when the hospital is sufficiently benevolent. When the hospital is weakly benevolent, a mixed policy solving a trade-off between rent extraction, efficiency and dumping deterrence must be preferred. Following Mougeot and Naegelen (2008), we show how the optimal combination of fixed price and partially costbased payment depends on the degree of benevolence of the hospital, the social cost of public funds and the distribution of patients severity.
Keywords: I1; L3; D8; 330; hospital price regulation; outlier payment; piecewise mechanism